Mycorrhizal inoculants on sweet potato (Ipomoea batata) in Eutric Cambisol soils of Cuba - Espinosa-Cuéllar , Alberto; Rivera, Ramon; Varela-Nualles, Mario; Pérez-Díaz , Alberto (Agronomía Mesoamericana, 2023)
Introduction. The effective use of mycorrhizal inoculants poses a challenge for Cuban agriculture. Sweet potato is an important crop for human and animal nutrition, being a mycorrhizal crop with a successful breeding program. Objective. To determine whether all sweet potato cultivars respond to inoculation and if the effectiveness of inoculants varies among cultivars and planting seasons. Materials and methods. Two experiments were conducted during 2010 - 2012 in Eutric Cambisols in Villa Clara, Cuba, one for each planting season and repeated twice. Seventeen cultivars were evaluated for their response to the application of three inoculants, in the presence of a half the fertilization dose, and three non-inoculated treatments with fertilization levels of 0, 50, and 100 % of the nitrogen, phosphorus, and potassium dose (100 % NPK). A split plot design was used. Root yields, colonization frequency, and mycorrizal spore production were evaluated as response variables. Results. Cultivars responded positively to inoculation and fertilization, showing differences in yields. However, the highest yields were obtained when inoculated with Rhizoglomus irregulare/ INCAM-11, surpassing (p≤0.05) those obtained with only 50 % of the NPK dose. In the rainy season with higher yields, the differentiation between inoculants was more pronounced, and in thirteen and nine of the cultivars, yields obtained with INCAM-11 were higher (p≤0.05) to those obtained with Glomus cubense/ INCAM-4 and 100 % NPK, respectively. In the dry season, no significant differences were found between yields obtained by inoculating INCAM-11 or INCAM-4 or applying 100 % NPK. In both seasons, inoculation with Funneliformis mosseae/ INCAM-2 was consistently lower. Colonization frequencies and spore production were always higher (p≤0.05) when INCAM-11 was inoculated. Conclusion. Under these soil conditions evaluated, inoculation with INCAM-11 showed higher effectiviveness for all cultivars and planting seasons, resulting in a higher yields and mycorrhizal performance indicators.